Anode strip and application thereof

By combining silicon -based active substances and specific adhesives in the anode tablet, the problem of silicon particles in the anode polar film laser punching technology is solved, and the stability and life of the battery are improved.

CN119381402AActive Publication Date: 2025-01-28ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411390326.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-28
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

In the existing anode laser hole drilling technology, high-temperature etching may cause the silicon particles in the anode to be burned, affecting the long-term stability and consistency of the battery.

Method used

The use of an anode tablet includes a silicon -based active substance and adhesive. The adhesive consists of polyacrylic acid and its derivatives and polyethylene glycol. Make sure that the adhesive is in a rubber state at high temperature, and the protection of silicon particles is not excessively burned.

Benefits of technology

Effectively avoid excessive burning of silicon particles in non -perforated areas, improve the circulation and safety performance of the battery, and extend the life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides an anode strip and a secondary battery using the same, the anode strip comprises an anode active material layer, the anode active material layer comprises an anode active material and a binder, the anode active material comprises a silicon-based active substance, and the binder comprises polyacrylic acid and derivatives thereof and polyvinyl alcohol; the anode strip is punched by laser; when the mass content of the silicon-based active substance is a fixed value, the mass content of the polyvinyl alcohol is in direct proportion to the laser drilling power; and when the laser drilling power is a fixed value, the mass content of the polyvinyl alcohol is in direct proportion to the mass content of the silicon-based active substance. Compared with the prior art, the anode plate provided by the invention has the advantages that the anode plates containing the binders with different contents are selected according to different laser drilling powers or different silicon contents of the silicon anode plates, so that excessive burning of active substances at non-drilling positions of the silicon anode plates is avoided, and the cycle performance and the safety performance of the battery in the charge-discharge process are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of secondary batteries, and in particular to an anode sheet and application thereof. Background Art

[0002] In the existing lithium-ion battery manufacturing technology, the manufacture and design of the anode pole piece is a critical step. The specific process and material selection have an important impact on the battery's performance, such as energy density, charge / discharge rate, and life. In recent years, laser drilling of anode pole pieces has received widespread attention as a new manufacturing technology.

[0003] The anode plate laser drilling process uses a high-power density laser beam to irradiate the material being processed, rapidly heating the material to the vaporization temperature, and then evaporating to form holes. The emergence of this technology effectively improves the charging window of the battery cell and opens up a new way to improve the performance of lithium-ion batteries.

[0004] However, there are also some problems to be solved in the implementation of this technology. In particular, since the anode laser drilling requires the use of high temperature to burn and etch the pole piece, this may cause the silicon particles in the anode to be burned, thus affecting the long-term stability and consistency of the battery. Specifically, this may cause some problems in the later stages of the battery cycle, such as performance degradation and reduced lifespan.

[0005] Therefore, how to find and develop a method that can solve the problems in the existing anode electrode laser drilling technology and improve the performance and life of lithium-ion batteries has become an important task and research hotspot in this field. Summary of the invention

[0006] One of the purposes of the present invention is to provide an anode sheet to address the deficiencies of the prior art and solve the problem that high-power laser drilling causes high-temperature burning of active materials in the anode sheet except for the drilling positions.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] An anode sheet, comprising an anode active material layer, wherein the anode active material layer comprises an anode active material and a binder, wherein the anode active material comprises a silicon-based active substance, and the binder comprises polyacrylic acid and its derivatives and polyvinyl alcohol; and the anode sheet further comprises a hole penetrated by a laser;

[0009] The glass transition temperature of the polyacrylic acid and its derivatives is greater than that of polyvinyl alcohol, and the mass content of the polyvinyl alcohol in the binder, the mass content of the silicon-based active substance in the anode active material and the power of the laser drilling satisfy at least one of the following relationships:

[0010] (a) When the mass content of the silicon-based active substance is a constant value, the mass content of the polyvinyl alcohol is directly proportional to the power of the laser drilling;

[0011] (b) When the power of the laser drilling is a constant value, the mass content of the polyvinyl alcohol is directly proportional to the mass content of the silicon-based active substance.

[0012] Preferably, when the mass content of the silicon-based active substance is 1 to 5%, the mass content of the polyvinyl alcohol and the power of the laser drilling satisfy the following relationship:

[0013] When the laser drilling power is less than 200W, the mass content of the polyvinyl alcohol is 0.1% to 3%;

[0014] When the laser drilling power is 200W to 700W, the mass content of the polyvinyl alcohol is 3% to 10%;

[0015] When the laser drilling power is 700W to 1500W, the mass content of the polyvinyl alcohol is 10% to 35%;

[0016] When the laser drilling power is greater than 1500W, the mass content of the polyvinyl alcohol is 35% to 50%.

[0017] Preferably, when the laser drilling power is 700W to 1500W, the mass content of the polyvinyl alcohol and the mass content of the silicon-based active substance satisfy the following relationship:

[0018] The mass content of the silicon-based active substance is 1-5%, and the mass content of the polyvinyl alcohol is 10-35%;

[0019] The mass content of the silicon-based active substance is 5% to 10%, and the mass content of the polyvinyl alcohol is 35% to 50%;

[0020] The mass content of the silicon-based active substance is greater than 10%, and the mass content of the polyvinyl alcohol is 50% to 75%.

[0021] Preferably, when the laser drilling power is less than 200 W, the mass content of the polyvinyl alcohol is 0.1-3%, and the hole depth of the laser drilling is less than 10 μm.

[0022] Preferably, when the laser drilling power is 200W to 700W, the mass content of the polyvinyl alcohol is 3% to 10%; and the hole depth of the laser drilling is 10 to 15 μm.

[0023] Preferably, when the laser drilling power is 700W to 1500W, the mass content of the polyvinyl alcohol is 10% to 35%, and the hole depth of the laser drilling is 15 to 20 μm.

[0024] Preferably, when the laser drilling power is greater than 1500 W, the mass content of the polyvinyl alcohol is 35% to 50%, and the hole depth of the laser drilling is greater than 25 μm.

[0025] Preferably, the laser-drilled hole has a depth of 15 to 20 μm.

[0026] Preferably, the mass ratio of the polyvinyl alcohol to the polyacrylic acid and its derivatives is (1-75):(25-99).

[0027] Preferably, the polyacrylic acid and its derivatives include at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, polyacrylamide and calcium polyacrylate.

[0028] Preferably, the silicon-based active substance includes at least one of silicon carbon, silicon oxygen, and nano-silicon; the anode active material also includes graphite particles, and the OI value of the graphite particles is 7-9.

[0029] The present invention also provides a secondary battery, comprising any one of the above-mentioned anode sheets.

[0030] Compared with the prior art, the beneficial effects of the present invention are as follows: the anode sheet of the present invention comprises an anode active material layer, the anode active material layer comprises an anode active material and a binder, the anode active material comprises a silicon-based active substance, the binder comprises polyacrylic acid and its derivatives and polyvinyl alcohol, and according to different laser drilling powers or different silicon contents of silicon negative electrode sheets, negative electrode sheets containing different contents of binder are selected, thereby avoiding excessive burning of active materials at non-drilled locations of the silicon negative electrode sheets, thereby improving the cycle performance and safety performance of the battery during the charge and discharge process.

[0031] Among them, the polyvinyl alcohol in the binder is a linear high molecular polymer, which has good adaptability with another binder, linear chain polyacrylic acid and its derivatives, effectively restraining the silicon particles in the pole piece and reducing the expansion effect of the silicon particles themselves caused by multiple charge and discharge. At the same time, during laser drilling, the polyvinyl alcohol added to the silicon negative electrode sheet has a lower glass transition temperature and can be blended with polyacrylic acid and its derivatives to reduce the overall glass transition temperature, so that the binder is in a rubber state. The rubber state of the material has higher fluidity and plasticity, that is, the fluid binder flows on the silicon particles, and the linear binder can wrap around the silicon particles. Therefore, when etching the silicon anode sheet, the probability of the silicon particles, that is, the active material, being etched and broken down is greatly reduced, thereby protecting the pole piece part where the laser drilling is not performed. DETAILED DESCRIPTION

[0032] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.

[0033] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0034] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.

[0035] According to a first aspect of the present invention, there is provided an anode sheet comprising an anode active material layer, wherein the anode active material layer comprises an anode active material and a binder, wherein the anode active material comprises a silicon-based active substance, and the binder comprises polyacrylic acid (PAA) and its derivatives and polyvinyl alcohol (PVA); the anode sheet is punched by laser.

[0036] The mass content of the polyvinyl alcohol in the binder, the mass content of the silicon-based active substance in the anode active material and the power of the laser drilling at least satisfy one of the following relationships:

[0037] (a) When the mass content of the silicon-based active substance is a constant value, the mass content of the polyvinyl alcohol is directly proportional to the power of the laser drilling;

[0038] (b) When the power of the laser drilling is a constant value, the mass content of the polyvinyl alcohol is directly proportional to the mass content of the silicon-based active substance.

[0039] The binder contained in the laser-punched anode sheet of the present invention includes polyacrylic acid and its derivatives and polyvinyl alcohol, and the amount thereof needs to be added according to the laser punching power and the content of silicon-based active substances in the silicon anode sheet, so as to prevent the electrode sheet from being burned by high temperature under high-power laser drilling. Polyvinyl alcohol is an important synthetic polymer material, and its molecular chain contains a large number of hydroxyl (-OH) functional groups. These hydroxyl groups interact with each other through hydrogen bonds to form an interlaced lattice structure, so it has good adhesion. The glass transition temperature of polyvinyl alcohol is generally between 60 and 85°C, while the glass transition temperature of polyacrylic acid and its derivatives is about 105°C to 155°C. The blending of the two can reduce the overall glass transition temperature.

[0040] When performing laser etching and drilling, the drilling power represents the etching intensity of the equipment on the electrode. The greater the drilling power, the deeper the drilling depth. As the drilling depth increases, the etching temperature will also become higher and higher, and the amount of polyvinyl alcohol required to be added needs to be increased accordingly. The temperature of the punched electrode rises suddenly, causing the binder to be in a rubber state. The rubber state of the material has high fluidity and plasticity, that is, the fluid binder flows on the silicon particles, and the linear binder can wrap around the silicon particles. Therefore, when etching the silicon anode sheet, the probability of the silicon particles, that is, the active material, being etched and broken down is greatly reduced; on the contrary, when the binder is in a glassy state, the material is hard and brittle, the silicon particles wrapped around itself have low bonding strength with the binder, the binder and the silicon particles are in a peeling state, and the probability of the silicon particles being etched increases.

[0041] It should also be noted that polyvinyl alcohol, as a linear high molecular polymer, has good adaptability with the linear chain PAA binder in the silicon anode sheet formula, which can effectively bind silicon particles and reduce the expansion effect of silicon particles caused by multiple charging and discharging.

[0042] In one embodiment of the present invention, when the mass content of the silicon anode sheet is 1-5%, and the laser drilling power is less than 200W, the mass content of the polyvinyl alcohol is 0.1-3%.

[0043] In one embodiment of the present invention, when the mass content of the silicon anode sheet is 1-5%, and the laser drilling power is 200W-700W, the mass content of the polyvinyl alcohol is 3%-10%.

[0044] In one embodiment of the present invention, when the mass content of the silicon anode sheet is 1-5%, and the laser drilling power is 700W-1500W, the mass content of the polyvinyl alcohol is 10%-35%.

[0045] In one embodiment of the present invention, when the mass content of the silicon anode sheet is 1-5%, and the laser drilling power is greater than 1500W, the mass content of the polyvinyl alcohol is 35%-50%.

[0046] In one embodiment of the present invention, when the laser drilling power is 700W-1500W, the mass content of the silicon-based active material is 1-5%, and the mass content of the polyvinyl alcohol is 10%-35%.

[0047] In one embodiment of the present invention, when the laser drilling power is 700W-1500W, the mass content of the silicon-based active material is 5%-10%, and the mass content of the polyvinyl alcohol is 35%-50%.

[0048] In one embodiment of the present invention, when the laser drilling power is 700W-1500W, the mass content of the silicon-based active material is greater than 10%, and the mass content of the polyvinyl alcohol is 50%-75%.

[0049] In the present invention, laser drilling is performed on the silicon anode sheet, and the hole depths left on the electrode sheet at different laser powers also have a certain numerical range. In some embodiments, when the laser drilling power is less than 200W, the mass content of polyvinyl alcohol is 0.1-3%, and the hole depth of the laser drilling is less than 10μm.

[0050] In some embodiments, when the laser drilling power is 700W to 1500W, the mass content of the polyvinyl alcohol is 10% to 35%, and the hole depth of the laser drilling is 15 to 20 μm.

[0051] In some embodiments, when the laser drilling power is greater than 1500 W, the mass content of the polyvinyl alcohol is 35% to 50%, and the hole depth of the laser drilling is greater than 25 μm.

[0052] In the present invention, the mass ratio of the binder polyvinyl alcohol to the polyacrylic acid and its derivatives in the active material layer on the laser-perforated anode sheet is (1-75): (25-99), and the specific ratios may be 1:99, (3-10): (90-97), (10-35): (65-90), (35-50): (50-65), (50-75): (25-50), and may include but are not limited to the above examples. The mass content of the polyvinyl alcohol is proportional to the laser perforation power and the content of the silicon-based active material in the silicon anode sheet.

[0053] In one embodiment of the present invention, the polyacrylic acid and its derivatives include at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, polyacrylamide and calcium polyacrylate, preferably polyacrylic acid.

[0054] In one embodiment of the present invention, the silicon-based active material includes at least one of silicon carbon, silicon oxygen, and nano-silicon, preferably silicon carbon.

[0055] In addition, the selection of the OI value (oxidation index) of the graphite in the anode active material of the present invention is critical. The matching graphite OI value of the present invention is selected in the range of 7 to 9, specifically 7.0, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.7, 7.8, 7.9, 8.0, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9, 9.0, and may include but are not limited to the above-mentioned values, preferably 8.6.

[0056] Among them, as the amount of polyvinyl alcohol changes, adjusting the graphite OI value to improve the distribution and interaction of the binder can improve the thermal stability of the anode active material, allowing it to maintain performance at higher temperatures. A moderate OI value can enhance the compatibility of graphite with the binder, improve the uniformity and stability of the electrode, and thus compensate for the adverse effects caused by excessive polyvinyl alcohol. Excessive polyvinyl alcohol will affect the slurry performance and electrode quality, and by adjusting the OI value of graphite, the interaction between graphite and the binder can be optimized, thereby balancing the effects of polyvinyl alcohol and improving the overall performance of the electrode.

[0057] The OI value of graphite in the present invention is obtained by X-ray diffraction (XRD) analysis. In one embodiment of the present invention, the anode active material, the conductive agent, and the binder are mixed in a weight ratio of (95.5-97.8): (0.1-1): (2.0-3.8) to prepare an anode active slurry; specifically, it can be 95.5:0.7:3.8, 96:0.5:3.5, 96.3:1:2.7, 96.5:0.1:3.4, 97.2:0.5:2.3, 97.5:0.4:2.1; it can include but not be limited to the above examples, preferably 97.2:0.5:2.3.

[0058] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.

[0059] Example 1

[0060] Preparation of anode electrode:

[0061] 1) mixing an anode active material (graphite with an OI value of 8.6 + 5% wt silicon carbon), a conductive agent (SWCNT + SP), and a binder (PAA + 2% PVA) in a weight ratio of 97.2%: 0.5%: 2.3% to prepare an anode active material slurry;

[0062] 2) coating the prepared anode active slurry on the current collector copper foil, cold pressing, and cutting into strips to obtain anode sheets;

[0063] 3) The anode sheet obtained in step 2) is punched with a laser power of 150W, and the hole depth is 5μm, so as to obtain the laser punched anode sheet. Preparation of cathode sheet: Active material LiCoO2, conductive agent acetylene black, conductive carbon nanotubes, binder polyvinylidene fluoride (PVDF) are fully dispersed and uniformly coated on the aluminum current collector in a weight ratio of 98.2%: 0.5%: 0.3%: 1.0% in N-methylpyrrolidone solvent system, and then cold pressed into strips to obtain cathode sheet.

[0064] The preparation parameters of the anode electrode are summarized in Table 1 below.

[0065] Isolation film: The PE surface is coated with a ceramic mixture as an isolation film.

[0066] Electrolyte: Ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) are mixed in a volume ratio of 1:1:4:4, and then fully dried lithium salt LiPF6 is dissolved in a mixed organic solvent at a ratio of 1 mol / L to prepare an electrolyte.

[0067] Preparation of soft-pack battery cells: The cathode electrode sheet, isolation film, and laser-punched anode sheet are wound or stacked to produce a bare battery cell, which is then packaged and injected with electrolyte to produce a finished lithium-ion battery.

[0068] Example 2-

[0069] The difference from Example 1 is that in step 1), PVA accounts for 5% of the total amount of the adhesive, and in step 3), the laser drilling power is 500 W and the hole depth is 12 μm.

[0070] The rest is the same as in Example 1 and will not be described again here.

[0071] Example 3

[0072] The difference from Example 1 is that in step 1), PVA accounts for 25% of the total amount of the adhesive, and in step 3), the laser drilling power is 1200 W and the hole depth is 18 μm.

[0073] The rest is the same as in Example 1 and will not be described again here.

[0074] Example 4

[0075] The difference from Example 1 is that in step 1), PVA accounts for 45% of the total amount of the adhesive, and in step 3), the laser drilling power is 1800 W and the hole depth is 28 μm.

[0076] The rest is the same as in Example 1 and will not be described again here.

[0077] Example 5

[0078] The difference from Example 3 is the added anode active material (graphite + 8 wt% silicon carbon) and PVA in the binder accounting for 45% of the total binder.

[0079] The rest is the same as in Example 3 and will not be described again here.

[0080] Example 6

[0081] The difference from Example 3 is the added anode active material (graphite + 15 wt% silicon carbon) and PVA in the binder accounting for 65% of the total binder.

[0082] The rest is the same as in Example 3 and will not be described again here.

[0083] Comparative Examples 1-3

[0084] The difference from Example 2 is the amount of PVA added as the binder in step 1), as shown in Table 1;

[0085] The rest is the same as in Example 2 and will not be described again here.

[0086] Comparative Examples 4-6

[0087] The difference from Example 3 is the amount of binder PVA added in step 1), as shown in Table 1;

[0088] The rest is the same as in Example 3 and will not be described again here.

[0089] Comparative Examples 7-9

[0090] The difference from Example 5 is the amount of the binder PVA added in step 1), as shown in Table 1;

[0091] The rest is the same as in Example 5 and will not be described again here.

[0092] Comparative Examples 10-11

[0093] The difference from Example 6 is the amount of the binder PVA added in step 1), as shown in Table 1;

[0094] The rest is the same as in Example 6 and will not be described again here.

[0095] Comparative Example 12

[0096] The difference from Example 4 is that in the binder of step 1), PVA accounts for the total amount of the binder, as shown in Table 1;

[0097] The rest is the same as in Example 4 and will not be described again here.

[0098] Comparative Example 13

[0099] The difference from Example 1 is that PVA accounts for the total amount of the binder in step 1), as shown in Table 1;

[0100] The rest is the same as in Example 1 and will not be described again here.

[0101] Comparative Example 14

[0102] The difference from Example 3 is the laser drilling power and hole depth in step 3), as shown in Table 1;

[0103] The rest is the same as in Example 3 and will not be described again here.

[0104] Comparative Example 15

[0105] The difference from Example 4 is the laser drilling power and hole depth in step 3), as shown in Table 1;

[0106] The rest is the same as in Example 4 and will not be described again here.

[0107] Comparative Example 16

[0108] The difference from Example 5 is the laser drilling power and hole depth in step 3), as shown in Table 1;

[0109] The rest is the same as in Example 5 and will not be described again here.

[0110] Comparative Examples 17-18

[0111] The difference from Example 3 is the OI value of the graphite in step 1), as shown in Table 1;

[0112] The rest is the same as in Example 3 and will not be described again here.

[0113] Comparative Example 19

[0114] The difference from Example 3 is that the PVA in the binder of step 1) is replaced by styrene-butadiene rubber;

[0115] The rest is the same as in Example 3 and will not be described again here.

[0116] The soft-pack batteries of Examples 1 to 6 and Comparative Examples 1 to 19 were respectively subjected to cycle performance tests, and the test results are shown in Table 1.

[0117] Test method: The battery cell is charged to 4.25V at 4.0C step rate, and then charged to the cut-off voltage at 3.0C. After 800 cycles, the remaining capacity is the percentage of the initial capacity, i.e. the capacity retention rate %.

[0118] The test method for the graphite OI value is: OI=C002 / C110, wherein C002 is the peak area of ​​the 002 characteristic diffraction peak in the X-ray diffraction spectrum of the negative electrode active material powder, and C110 is the peak area of ​​the 110 characteristic diffraction peak in the X-ray diffraction spectrum of the negative electrode active material powder.

[0119] Table 1

[0120]

[0121]

[0122] Analysis of results: In Examples 1-6 within the scope of the present invention, two binders, PAA and PVA, are added at the same time. PVA, as a linear high molecular polymer, has good compatibility with the linear chain PAA binder in the silicon anode sheet formula, can effectively bind silicon particles, reduce the expansion effect of silicon particles caused by multiple charge and discharge, effectively protect the capacity retention rate of the electrode sheet and improve the safety performance of the electrode sheet, and avoid high temperature generated during laser drilling and burning of silicon particles, resulting in capacity failure.

[0123] From Comparative Examples 4-9, it can be seen that the amount of PVA added is limited in range, and its effect changes roughly in a parabolic manner. If the amount added is too low, the best effect cannot be achieved, and excessive addition may even cause the capacity retention rate to deteriorate. From Comparative Examples 12-16, if any of the contents of the binder PAA and PVA, the punching power, and the punching depth are not within the range of the present invention, the capacity retention rate deteriorates significantly.

[0124] It can be seen from comparative examples 2-3, 5-6, 9, and 13-16 that too much PVA will reduce the bonding strength of the electrode and the electrochemical performance of the battery cell. On the one hand, too much polyvinyl alcohol will increase the viscosity of the slurry and affect the coating uniformity. On the other hand, too high a content will easily cause the slurry to crack during the drying process, affecting the performance of the anode sheet. Therefore, polyvinyl alcohol needs to be controlled within a reasonable range according to the silicon content and the laser drilling power.

[0125] It can be seen from Comparative Example 19 that although the Tg (glass transition temperature) of styrene-butadiene rubber is lower than that of polyvinyl alcohol, in the laser drilling of the anode pole piece, the adhesion and tensile strength of styrene-butadiene rubber do not meet the specific requirements of the anode pole piece during the laser drilling process. The anode pole piece needs to maintain good structural integrity after laser drilling, which requires the adhesive to have sufficient bonding strength. Due to insufficient adhesion, styrene-butadiene rubber causes the pole piece to delaminate or peel after drilling, affecting battery performance and safety. The thermal stress and mechanical stress generated during the laser drilling process may cause stretching of the material. Due to the insufficient tensile strength of styrene-butadiene rubber, it cannot effectively resist these stresses, resulting in cracks or breaks in the pole piece during or after the drilling process.

[0126] In summary, the present invention adjusts the amount of PVA in the binder according to the laser drilling power and the silicon-carbon content of the silicon anode sheet, so that the electrode sheet in the non-laser drilling area is not burned by the high temperature generated by the high-power laser, which can effectively ensure the capacity retention rate of the battery and improve the cycle performance and safety performance of the battery during the charge and discharge process.

[0127] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. An anode sheet, characterized in that: The anode active material layer includes an anode active material and a binder, wherein the anode active material includes a silicon-based active substance, and the binder includes polyacrylic acid and its derivatives and polyvinyl alcohol; the anode sheet is punched by laser; The glass transition temperature of the polyacrylic acid and its derivatives is greater than that of polyvinyl alcohol, and the mass content of the polyvinyl alcohol in the binder, the mass content of the silicon-based active substance in the anode active material and the power of the laser drilling satisfy at least one of the following relationships: (a) When the mass content of the silicon-based active substance is a constant value, the mass content of the polyvinyl alcohol is directly proportional to the power of the laser drilling; (b) When the power of the laser drilling is a constant value, the mass content of the polyvinyl alcohol is directly proportional to the mass content of the silicon-based active substance.

2. The anode sheet according to claim 1, characterized in that: When the mass content of the silicon-based active substance is 1-5%, the mass content of the polyvinyl alcohol and the power of the laser drilling satisfy the following relationship: When the laser drilling power is less than 200W, the mass content of the polyvinyl alcohol is 0.1% to 3%; When the laser drilling power is 200W to 700W, the mass content of the polyvinyl alcohol is 3% to 10%; When the laser drilling power is 700W to 1500W, the mass content of the polyvinyl alcohol is 10% to 35%; When the laser drilling power is greater than 1500W, the mass content of the polyvinyl alcohol is 35% to 50%.

3. The anode sheet according to claim 1, characterized in that: When the laser drilling power is 700W to 1500W, the mass content of the polyvinyl alcohol and the mass content of the silicon-based active substance satisfy the following relationship: The mass content of the silicon-based active substance is 1-5%, and the mass content of the polyvinyl alcohol is 10-35%; The mass content of the silicon-based active substance is 5% to 10%, and the mass content of the polyvinyl alcohol is 35% to 50%; The mass content of the silicon-based active substance is greater than 10%, and the mass content of the polyvinyl alcohol is 50% to 75%.

4. The anode sheet according to claim 2, characterized in that: When the laser drilling power is less than 200W, the mass content of the polyvinyl alcohol is 0.1-3%, and the hole depth of the laser drilling is less than 10 μm.

5. The anode sheet according to claim 2, characterized in that: When the laser drilling power is 200W-700W, the mass content of the polyvinyl alcohol is 3%-10%; the hole depth of the laser drilling is 10-15 μm.

6. The anode sheet according to claim 2, characterized in that: When the laser drilling power is 700W to 1500W, the mass content of the polyvinyl alcohol is 10% to 35%, and the hole depth of the laser drilling is 15 to 20 μm.

7. The anode sheet according to claim 2, characterized in that: When the laser drilling power is greater than 1500W, the mass content of the polyvinyl alcohol is 35% to 50%, and the hole depth of the laser drilling is greater than 25 μm.

8. The anode sheet according to claim 3, characterized in that: The laser drilling hole depth is 15-20 μm.

9. The anode sheet according to claim 1, characterized in that: The mass ratio of the polyvinyl alcohol to the polyacrylic acid and its derivatives is (1-75):(25-99).

10. The pole piece according to claim 1, characterized in that: The polyacrylic acid and its derivatives include at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, polyacrylamide and calcium polyacrylate.

11. The anode sheet according to claim 1, characterized in that: The silicon-based active material includes at least one of silicon carbon, silicon oxygen, and nano-silicon; the anode active material also includes graphite particles, and the OI value of the graphite particles is 7-9.

12. A secondary battery, characterized in that: The anode sheet comprises the anode sheet according to any one of claims 1 to 11.

Citation Information

Patent Citations

  • Lithium ion battery, negative plate thereof and preparation method thereof

    CN105304858A

  • Binder, preparation method of binder, electrode plate and secondary battery

    CN112680148A

  • Preparation method of lithium ion battery with porous carbon-supplemented lithium negative pole piece

    CN114221045A

  • Negative pole piece and preparation method thereof, battery monomer, battery and power utilization device

    CN116230869A

  • Secondary battery, electronic device and preparation method of secondary battery

    CN116802870A